ASERTIF TRAINING MENINGKATKAN KOMUNIKASI INTERPERSONAL SISWA SMKN X - Astinah Astinah (fakultas Ushuluddin dan Dakwah IAIN Bone, 2018)
This research is an experimental research with the aim of providing treatment in the form of assertive training interventions to improve interpersonal communication skills of class X students majoring in Marketing at SMKN X. This research uses a quasi experimental design with nonrandomized pretest-posttest control group design. The data are collected through observation, interviews, FGD, and interpersonal communication scale (Puspitasari, 2012). The data are analyzed by using SPSS 16 for windows with non-parametric statistical analysis paired sample t-test. The results showed that assertive training improved students' interpersonal communication skills. This can be observed from the statistical analysis between pre-test and post-test obtained p = 0.000 (p 0.05). In addition, an increase also occurred in the results of statistical analysis between post test and follow up with a value of p = 0.000 (p 0.05).KeywordsInterpersonal Communication; Assertive; Assertive Training; SMKN Students